2023
DOI: 10.3390/rs15092250
|View full text |Cite
|
Sign up to set email alerts
|

Integrating GIS, Remote Sensing, and Citizen Science to Map Oak Decline Risk across the Daniel Boone National Forest

Abstract: Oak decline is a general term used for the progressive dieback and eventual mortality of oak trees due to many compounding stressors, typically a combination of predisposing, inciting, and contributing factors. While pinpointing individual causes of decline in oak trees is a challenge, past studies have identified site and stand characteristics associated with oak decline. In this study, we developed a risk map of oak decline for the Daniel Boone National Forest (DBNF), combining GIS, remote sensing (RS), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Then, each evaluation indicator was graded, assigning 1, 2, and 3 to the low, medium, and high grades, respectively (Table 3). Among them, the grading of terrain slope, surface soil texture, and distance to roads referred to the relevant national standards and previous studies [40], while the grading of other indicators was based on the Jenks grading method [52]. Finally, the weights and scores of each evaluation indicator were summarized to calculate the cropland quality index with a range of 1 to 3.…”
Section: Indicator System For Cropland Quality Evaluationmentioning
confidence: 99%
“…Then, each evaluation indicator was graded, assigning 1, 2, and 3 to the low, medium, and high grades, respectively (Table 3). Among them, the grading of terrain slope, surface soil texture, and distance to roads referred to the relevant national standards and previous studies [40], while the grading of other indicators was based on the Jenks grading method [52]. Finally, the weights and scores of each evaluation indicator were summarized to calculate the cropland quality index with a range of 1 to 3.…”
Section: Indicator System For Cropland Quality Evaluationmentioning
confidence: 99%
“…Also, there is a complex interplay between climatic parameters and various biotic stressors, highlighting the multifaceted nature of oak decline and the need for targeted conservation efforts to mitigate its adverse effects 26 . Furthermore, Hernández-Lambraño et al 15 and Crocker et al 28 indicated the risk of oak decline is exceptionally high in mid and upper slopes, south-facing aspects with high solar radiation, and steep convex slope segments with a dry soil moisture regime.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of satellite images with a wide range of spatial resolutions has opened possibilities for implementing multiscale approaches in remote sensing forestry applications. These approaches are particularly valuable for detecting and discriminating various objects within complex natural scenes, such as the dynamic processes of forest disturbances (Marceau & Hay 1999, Crocker et al 2023. Moreover, the spectral signatures of satellite image bands offer valuable information for detecting, identifying, and classifying various forms of tree damage caused by biotic or abiotic factors (El Ahmadi et al 2023).…”
Section: Introductionmentioning
confidence: 99%